2023
DOI: 10.1002/adma.202303642
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Mesenchymal Stem Cell Derived Exosomes Promote Keratinocytes and Fibroblasts Embedded in Collagen/Platelet‐Rich Plasma Scaffold and Accelerate Wound Healing

Abstract: Engineered skin substitutes derived from human skin significantly reduce inflammatory reactions mediated by foreign/artificial materials and are consequently easier to use for clinical application. Type I collagen is a main component of the extracellular matrix during wound healing and has excellent biocompatibility, and platelet‐rich plasma can be used as the initiator of the healing cascade. Adipose mesenchymal stem cell derived exosomes are crucial for tissue repair and play key roles in enhancing cell rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In general terms, it was observed here that treatment with Plasma + BM-MNC accelerated wound healing. This result is in line with the findings of several research groups using a scaffold alone or in combination with cells 10 or even exosomes, such as recently reported by Wang et al 28 . These authors used a collagen/platelet-rich plasma scaffold containing adipocyte-derived exosomes and detected faster wound healing than without treatment.…”
Section: Discussionsupporting
confidence: 92%
“…In general terms, it was observed here that treatment with Plasma + BM-MNC accelerated wound healing. This result is in line with the findings of several research groups using a scaffold alone or in combination with cells 10 or even exosomes, such as recently reported by Wang et al 28 . These authors used a collagen/platelet-rich plasma scaffold containing adipocyte-derived exosomes and detected faster wound healing than without treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Notable advancements in tissue regeneration encompassing the skin, bone, cartilage, nerves, and tendons have demonstrated the system's efficacy ( Table 5 ). For instance, for skin regeneration, the exosomes could promote cell proliferation and angiogenesis and accelerate the healing [ 175 , 228 , 229 ]. For bone and cartilage regeneration, such systems could facilitate tissue repair by providing osteogenic and chondrogenic factors [ 230 ].…”
Section: Application Of the Hydrogel-exosome System For Tissue Repair...mentioning
confidence: 99%
“… Regulation of fibroblast proliferation and differentiation: Fibroblasts, as the primary cellular component of loose connective tissue, originate from mesenchymal cells during embryonic development and play pivotal roles in hair follicle initiation and scar formation during wound healing [ 239 ]. ADSC-Exos can boost the proliferation capacity of fibroblasts in vitro and within the wound area, increasing the expression of ki67 [ 228 ]. Additionally, they may increase the mRNA levels of genes encoding α-smooth muscle actin (α-SMA) and fibroblast growth factor-2 (FGF-2) [ 240 ].…”
Section: Application Of the Hydrogel-exosome System For Tissue Repair...mentioning
confidence: 99%
“…Exosomal functions have been extensively studied, and the possibility of controlling tissue repair and regeneration is becoming increasingly important; for example, exosomes could be an attractive alternative to numerous cell and tissue engineering techniques 28 . For instance, several investigations of mesenchymal stem cell (MSC) transplantation for tissue regeneration have shown that MSCs primarily alter cells through paracrine signaling mediated by the exosomes they release 29 , 30 . Thus, a cell-free approach that uses paracrine agents, such as exosomes, to encourage tissue repair and regeneration would avoid the potential risks of direct stem cell transplantation, including teratomas, immunological rejection, and the decreased capacity of the engrafted cells to mediate tissue regeneration 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%